THE INFLUENCE OF WORKLOAD AND WORK-FAMILY CONFLICT ON JOB STRESS WITH FAMILY SOCIAL SUPPORT AS A MODERATING VARIABLE AMONG EMPLOYEES OF PT BANK NEGARA INDONESIA (PERSERO) TBK PALEMBANG REGIONAL OFFICE - Wildan Ulil Albab; Fereshti Nurdiana Dihan (Publikasi Inspirasi Indonesia, 2026)
This research aims to examine and analyze the influence of workload and work-family conflict on job stress, with family social support as a moderating variable. This study was conducted on employees at PT Bank Negara Indonesia (Persero) TBK Palembang Regional Office with a sample size of 150 respondents. Data collection was carried out by distributing questionnaires using a 1-5 Likert Scale. Data analysis used the quantitative SEM-PLS (Structural Equation Modeling-Partial Least Square) method with Smart-PLS software. The results showed that workload has a significant positive effect on job stress. Work-family conflict significantly affects job stress. Family social support has a significant negative effect on job stress. Family social support is proven to moderate the relationship between workload, work-family conflict, and job stress.